2020
DOI: 10.3390/sym12061020
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive View on Racing Car Upright Design and Manufacturing

Abstract: This paper deals with the design of an upright using a topological optimization. This type of optimization is a relatively young and rapidly evolving area of computational mechanics that seeks to make multiple material savings that cannot be achieved by conventional methods. The optimized upright was utilized in a fully functional prototype of the student formula within the Formula Student competition. The main objective of the optimization was to meet the requirements of the physical properties, weight, stiff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…Among the designable components, there are the bell crank, suspension link, rear upright, etc. [2][3][4][5]. The impact attenuator (IA) is as well in this category, and is defined as a deformable, energy-absorbing device mounted forward of the car's front [6].…”
Section: Introductionmentioning
confidence: 99%
“…Among the designable components, there are the bell crank, suspension link, rear upright, etc. [2][3][4][5]. The impact attenuator (IA) is as well in this category, and is defined as a deformable, energy-absorbing device mounted forward of the car's front [6].…”
Section: Introductionmentioning
confidence: 99%
“…The paper by Marsalek et al [10] demonstrated the capability of the SLS method for the production of flexible structures with complex geometries while using the PA12 (Polyamide 12) material. Other examples of printing complex geometries using TOP have been published by Jancar et al [11,12]. However, these papers use a different printing method, namely Selective laser melting (SLM)-a method that is similar to SLS, which, however, prints metal alloys and requires supports.…”
Section: Connecting Adaptermentioning
confidence: 99%
“…3D printing technology has enabled designers to fabricate parts that are functional, lighter, and remarkably more complex from various materials [1][2][3]. Remarkably, for metallic parts fabricated with the selective laser melting (SLM) method, the mechanical properties are higher in comparison with traditionally produced ones [4,5].…”
Section: Introductionmentioning
confidence: 99%